Industrial Revolution 4.0 can help boost construction industry - Adeleke, Adekunle Qudus (The New Straits Times Press (M) Bhd., 2020)
While the coronavirus has coused a setback to the world's economy as nations are forced into lockdown, it is different for the construction industry where workers are expected to work on site either to perform or oversee ongoing projects.